2017
DOI: 10.1186/s40662-017-0081-y
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes 24 months after LaserACE

Abstract: BackgroundTo evaluate the effects on near and intermediate visual performance after bilateral Laser Anterior Ciliary Excision (LaserACE) procedure.MethodsLaserACE surgery was performed using the VisioLite 2.94 μm erbium: yttrium–aluminum–garnet (Er:YAG) ophthalmic laser system in 4 oblique quadrants on the sclera over the ciliary muscle in 3 critical zones of physiological importance (over the ciliary muscles and posterior zonules) with the aim to improve natural dynamic accommodative forces. LaserACE was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…15,16 A preliminary study on 52 eyes with 24-month follow-up after the LaserACE reported that the binocular UNVA, binocular distance-corrected near visual acuity, and stereoacuity significantly improved postoperatively, and there was no significant change of best-corrected distance visual acuity. 17 However, the underlying wound remodeling that may affect the treatment efficacy and stability has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 A preliminary study on 52 eyes with 24-month follow-up after the LaserACE reported that the binocular UNVA, binocular distance-corrected near visual acuity, and stereoacuity significantly improved postoperatively, and there was no significant change of best-corrected distance visual acuity. 17 However, the underlying wound remodeling that may affect the treatment efficacy and stability has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…26 Cadaveric porcine eyes were used to optimize the laser intensity with respect to the depth of the micropores, which will affect the treatment efficacy. 16,17 The micropores were at approximately 63.5% of scleral thickness when the intensity was set at 12 pulses/pore.…”
Section: Discussionmentioning
confidence: 99%
“…The primary risk is accidental micro perforation of the sclera, however, the advantage of this procedure is that the cornea and the crystalline remains untouched and allows LaserACE ® to be performed after or even in combination with other procedures. [ 134 ]…”
Section: Discussionmentioning
confidence: 99%
“…a ) The three critical zones of significance as measured from the anatomical limbus; b ) Restored mechanical efficiency and improved biomechanical mobility (procedure objectives). Reprinted with permission from [ 50 ]
Fig. 3 LaserACE surgical technique.
…”
Section: Reviewmentioning
confidence: 99%
“…Photo a ) Quadrant marker; b ) Matrix marker; c ) Corneal Shield; d ) LaserACE micropore ablation; e ) Subconjunctival Collagen f ) Completed 4 quadrants. Reprinted with permission from [ 50 ]
Fig. 4 Uncorrected (lightly colored) and distance-corrected (darkly colored) visual acuity at a distance 4 m, intermediate (60 cm), and near (40 cm) for a ) Monocular and b ) Binocular patient eyes.
…”
Section: Reviewmentioning
confidence: 99%